2018
DOI: 10.1038/s41580-018-0007-0
|View full text |Cite|
|
Sign up to set email alerts
|

Contextual determinants of TGFβ action in development, immunity and cancer

Abstract: Few cell signals match the impact of the transforming growth factor-β (TGFβ) family in metazoan biology. TGFβ cytokines regulate cell fate decisions during development, tissue homeostasis and regeneration, and are major players in tumorigenesis, fibrotic disorders, immune malfunctions and various congenital diseases. The effects of the TGFβ family are mediated by a combinatorial set of ligands and receptors and by a common set of receptor-activated mothers against decapentaplegic homologue (SMAD) transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
655
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 638 publications
(698 citation statements)
references
References 201 publications
5
655
2
1
Order By: Relevance
“…In the liver, TIME TGFβ may suppress anti-tumour immune responses in several ways, by promoting Th2 vs Th1 response, by favouring the differentiation of macrophages into pro-tumorigenic M2-type and of naive CD4 + T-cells into Tregs, and by inhibiting the effector function of CD8 + T cells and NK cells. 96 TGFβ is also directly involved in the development and progression of solid tumours. In liver tissue it plays a major role in liver inflammation and fibrosis progression, through the activation of HSCs, which are the main producers of TGFβ.…”
Section: Soluble Mediators Of the Tumour Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the liver, TIME TGFβ may suppress anti-tumour immune responses in several ways, by promoting Th2 vs Th1 response, by favouring the differentiation of macrophages into pro-tumorigenic M2-type and of naive CD4 + T-cells into Tregs, and by inhibiting the effector function of CD8 + T cells and NK cells. 96 TGFβ is also directly involved in the development and progression of solid tumours. In liver tissue it plays a major role in liver inflammation and fibrosis progression, through the activation of HSCs, which are the main producers of TGFβ.…”
Section: Soluble Mediators Of the Tumour Microenvironmentmentioning
confidence: 99%
“…In liver tissue it plays a major role in liver inflammation and fibrosis progression, through the activation of HSCs, which are the main producers of TGFβ. 96 In the early stages of hepatocarcinogenesis, TGFβ has tumour suppressive functions inhibiting cell proliferation and stimulating apoptosis. 97 Conversely, after cell transformation has occurred, the cytokine promotes apoptosis resistance and cell proliferation 97 together supporting tumour progression and dissemination.…”
Section: Soluble Mediators Of the Tumour Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…TGFBs, activins, myostatin and nodal induce the phosphorylation of R-SMAD2 or 3, while BMPs mediate their activity through R-SMAD1, 5 or 8. All R-SMADs bind to SMAD4, an essential component for the generation of SMAD transcriptional responses [11][12][13] . Previous studies have demonstrated a role for some TGFβ ligands in myogenesis.…”
Section: A High Throughput Assay Identifies Novel Regulator Of Myoblamentioning
confidence: 99%
“…[13] All these secreted substances together result in the enhancement of collagen deposition, the remodeling of ECM and the formation of dense stromal TME. [18] Apart from this, TGF-β also plays a substantial role in the recruitment, activation and infiltration of macrophages, myeloid-derived suppressor cells and regulatory T (Treg) cells in TME, especially in the induction of M2 macrophages polarization. [19] Therefore, we speculated that regulating the TGF-β signal pathway to inactivate CAFs and inhibit M2 polarization might remodel the TME and enhance the intratumor drug penetration.…”
Section: Introductionmentioning
confidence: 99%